Thermochromic phase change film with repairable function as well as preparation method and application of thermochromic phase change film
Through the cross-linking of PVA and BA and the hydrogen bonding and chemical bonding of PEG-8000, a thermochromic phase change film is prepared by a one-step physical casting method, which solves the problems of complex preparation process and lack of repairability in the prior art, realizes the repairability, thermochromicity and phase change of the film material, and improves the thermal conductivity and cyclic stability.
Patent Information
- Application Number
- CN202411847202.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-25
AI Technical Summary
The existing thermochromic phase change materials are complex in the preparation process and are not repairable, cannot be effectively applied to irregular planes, and the microcapsule packaging causes the material to be unable to achieve uniform distribution during physical pouring.
The thermal conductivity path is constructed by cross-linking between PVA and BA, and hydrogen bonds and chemical bonds are formed with PEG-8000, and a thermochromic phase change film is prepared in one-step method for physical casting, and a thermochromic ink is added to achieve reversible thermochromic function.
The repairability, thermochromicity and phase changeability of the film material are achieved, and the thermal conductivity and cycle stability are good, while avoiding the uniform distribution problem caused by microcapsule packaging.
Smart Images

Figure CN119505459A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of film materials, and in particular to a thermochromic phase-change film with a repairable function and a preparation method and application thereof. Background Art
[0002] Organic phase change materials have the characteristics of high thermal energy storage density and constant conversion temperature. Combining organic phase change materials with reversible thermochromic materials can obtain reversible thermochromic phase change materials. For example, in existing literature 1 (Li BX, Luo Z, Yang WG, et al. Adaptive and adjustable MXene / reduced graphene oxide hybrid aerogel composites integrated with phase-change material and thermochromic coating for synchronous visible / infrared camouflages [J]. ACS nano, 2023, 17 (7): 6875-6885.), MXene dispersion and GO suspension are ultrasonically mixed and ascorbic acid is added for pre-reduction and hydrothermal assembly, the obtained hydrogel is directionally frozen and then freeze-dried to obtain aerogel, n-octadecane is adsorbed to obtain a composite phase change material, and then the composite phase change material is sprayed with thermochromic ink, and finally a thermochromic composite phase change material is obtained. Although this method obtains a thermochromic composite phase change material, this technical solution not only has the problem of complex preparation procedures, but also has the problem of fixed shape and non-repairability of the load matrix. Therefore, it is impossible to realize application on irregular planes and repair after damage.
[0003] In order to solve the problem of application on irregular planes, it can be achieved by preparing thermochromic phase change film materials. For example, in the existing document 2 (He Y, Sun S, Han N, et al. Thermal energy regulated and thermochromic composite film with temperature-sensitive "breathable" stomata [J]. Journal of Materials Science, 2020, 55: 12921-12939.), CVL and BPA are dissolved in tetradecanol to prepare capsule core materials, and then the core material and SMA solution are emulsified to obtain a prepolymer. Finally, the pH value of the mixed solution is adjusted with NaOH solution to obtain a microcapsule dispersion, and then the microcapsule dispersion is mixed with PVA and WPU solutions and electrospun to obtain a thermochromic nanofiber membrane. The enthalpy value of the obtained phase change film is 44.9 J / g. Although this solution obtains a thermochromic composite phase change film, this technical solution also has the problem of complicated preparation procedures and is not repairable. In addition, the obtained phase change material is encapsulated by microcapsules - such technical solutions based on microcapsule technology have the following problems. Common microcapsules, such as microcapsules prepared by CVL, BPA and tetradecanol, have the characteristic that the obtained microcapsules are insoluble in water. This characteristic directly leads to the inability to achieve uniform distribution of such microcapsules when preparing thin film materials by physical casting.
[0004] Among them, in order to make the film material have repairable properties, a material with repair properties can be used as a matrix. For example, existing document 3 (Deng C, Dong H, Kou Y, et al. Flexible self-healing phase change film with high transition enthalpy for thermal management [J]. Journal of Energy Storage, 2023, 62: 106873.) PVA and PVP are each dissolved in deionized water and stirred to prepare a solution, and the two are mixed to obtain a hydrogel, and then erythritol is added to the hydrogel and stirred and mixed, and then poured into a glass plate and dried to obtain a composite phase change film material, and the enthalpy of the phase change film material is 191.5 J / g. This technical solution constructs a hydrogen bond network through PVA and PVP, which can provide excellent self-healing properties and recyclability, and gives the phase change film excellent flexibility, which can meet the application of irregular contours. This technical solution successfully prepared a phase change film with repairable properties, but the technical problem that this technical solution cannot be directly combined with thermochromic materials. Summary of the invention
[0005] The purpose of the present invention is to provide a thermochromic phase change film with a repairable function and a preparation method and application thereof. The technical problems existing in the prior art are solved by the following principles:
[0006] 1. Using the unstable hydrogen bond characteristics of PVA, a thin film material with repairable function is prepared through a simple physical casting one-step method. The obtained thin film material can be applied to various irregular planes; at the same time, due to the cross-linking effect between BA and PVA, a good thermal conductivity path can be constructed to improve the thermal conductivity of the phase change film; the addition of thermochromic ink can provide the phase change film with reversible thermochromic function;
[0007] 2. Chemical bonds and hydrogen bonds can be formed between PVA and PEG-8000. Different from traditional vacuum impregnation phase change materials, PEG-8000 can be firmly combined through the action of hydrogen bonds and chemical bonds, making it less likely to leak.
[0008] To achieve the above object, the present invention is implemented through the following technical solutions:
[0009] A thermochromic phase-change film with a repairable function, using polyvinyl alcohol (PVA) and boric acid (BA) as raw materials for cross-linking, thermochromic ink as a color-changing material, and polyethylene glycol (PEG-8000) as a phase-change material, to prepare a thermochromic film (PBTP-M) with a repairable function through a one-step method based on physical casting; the film has repairability, thermochromic properties, and phase-change properties.
[0010] The repairable property, that is, when used as a repairable material, when broken or damaged, it can be quickly restored to its original state by adding water and drying; the repairing operation of the repairable property is, first, overlapping the damaged film, then dripping water on the overlapped part, and finally drying at a drying temperature of 60°C and a drying time of 15 minutes, so that the damaged film can be reconnected, that is, repaired;
[0011] The thermochromic performance, that is, when used as a thermochromic material, under normal temperature conditions, the thermochromic phase change film is in a black opaque state; when the temperature is higher than 50°C, the thermochromic phase change film is in a colorless and transparent state, that is, when heated above 50°C, the thermochromic phase change film changes from a black opaque state to a colorless and transparent state; it is reversible, that is, after the thermochromic phase change film is heated to change from a black opaque state to a colorless and transparent state, when the temperature is lowered to room temperature, the thermochromic phase change film returns from a colorless and transparent state to a black opaque state;
[0012] The phase change performance, that is, when used as a phase change material, the phase change temperature is 22.67-53.76°C, the phase change enthalpy is 55.583-78.679 J / g, and the thermal conductivity is 0.6827-0.8643 W / (m·K).
[0013] A preparation method of a thermochromic phase change film with a repairable function, comprising the following steps: using a one-step method based on physical casting, with raw materials polyvinyl alcohol (PVA), boric acid (BA), thermochromic ink (TC) and PEG-8000 satisfying a certain mass ratio, firstly, under certain conditions, placing PVA in deionized water for magnetic stirring to obtain a PVA solution, then adding BA, TC and PEG-8000 to the PVA solution, continuing to perform magnetic stirring under certain conditions to obtain a PBTP mixed solution, finally, placing the PBTP solution in a mold for film laying, and drying under certain conditions, i.e., physical casting, to obtain a thermochromic phase change film PBTP-M with a repairable function, referred to as PBTP-M for short;
[0014] In the preparation method, the mass ratio of polyvinyl alcohol PVA, boric acid BA, thermochromic ink TC and PEG-8000 is 30:2:1:27, that is, the addition amount of PEG-8000 is 45wt.%;
[0015] In the preparation method, the stirring conditions for preparing the PVA solution are as follows: the stirring temperature is 75-80°C and the stirring time is 1.5-2h; the stirring conditions for preparing the PBTP mixed solution are as follows: the stirring temperature is 75-80°C and the stirring time is 1-1.5h;
[0016] In the preparation method, the drying conditions are as follows: the drying temperature is 60° C. and the drying time is 2-2.5 h.
[0017] The present invention has the following characteristics after experimental testing:
[0018] FTIR test shows that PBTP-M and PEG-8000 have the same characteristic peaks. The solution is successfully prepared by one-step physical casting. In addition, PEG-8000 and PVA are chemically bonded, and no new substances are produced.
[0019] XRD test showed that PBTP-M and PEG-8000 had the same characteristic peaks, and PBTP-M had no effect on the crystallization behavior of PEG-8000;
[0020] Macroscopic and SEM tests showed that PEG-8000 was evenly distributed in the PBTP-M film;
[0021] The deformation-recovery test shows that PBTP-M has arbitrary shape deformability;
[0022] The leakage test shows that PBTP-M has good anti-leakage performance and no leakage occurs at 80°C for 60 minutes;
[0023] Thermochromic tests show that PBTP-M has reversible thermochromic properties;
[0024] The simulated fracture-self-repair test showed that PBTP-M has repairable properties;
[0025] According to DSC test, the melting temperature of PBTP-M is between 51.97-53.76℃, the melting enthalpy is between 56.547-78.679J / g; the crystallization temperature is between 22.67-24.53℃, and the crystallization enthalpy is between 55.583-77.419J / g;
[0026] The DSC cycle test showed that PBTP-M has high cycle stability and thermal stability, and the enthalpy value of the cycle curve did not change significantly after 200 cycles;
[0027] The thermal conductivity test shows that PBTP-M has good thermal conductivity, with a thermal conductivity coefficient of 0.6827 to 0.8643 W / (m·K).
[0028] Therefore, the present invention has the following advantages over the prior art:
[0029] 1. There are hydrogen bonds and chemical bonds between PVA and PEG-8000, which make the two closely connected, thereby improving the anti-leakage performance of the phase change film;
[0030] 2. The phase change film has repairable properties and can be repaired and continued to be used after being broken;
[0031] 3 The thermochromic phase change film with repairable function prepared by the present invention has excellent thermal stability and cycle stability;
[0032] 4. The melting enthalpy of the phase change film is 56.547-78.679 J / g, and the crystallization enthalpy is 55.583-77.419 J / g, which has good heat storage performance per unit mass. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 FTIR graphs of PEG-8000, Comparative Example 1, Example 1, Example 2 and Example 3;
[0034] Figure 2 XRD patterns of PEG-8000, Comparative Example 1, Example 1, Example 2 and Example 3;
[0035] Figure 3The macroscopic observation diagrams of Comparative Example 1, Example 1, Example 2 and Example 3 are shown;
[0036] Figure 4 The SEM images of Comparative Example 1, Example 1, Example 2 and Example 3 are shown;
[0037] Figure 5 is the deformation-recovery diagram of Example 1;
[0038] Figure 6 The anti-leakage test diagrams of Comparative Example 1, Example 1, Example 2 and Example 3;
[0039] Figure 7 is the reversible thermochromic image of Example 1;
[0040] Figure 8 This is a simulated fracture-self-repair test diagram of Example 1;
[0041] Fig. 9 The DSC test graphs of PEG-8000, Comparative Example 1, Example 1, Example 2 and Example 3;
[0042] Fig.10 This is the DSC 200 cycle test diagram of Example 1;
[0043] Fig.11 The thermal conductivity diagram of PEG-8000, comparative example 1, example 1, example 2 and example 3. DETAILED DESCRIPTION
[0044] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0045] Example 1
[0046] A preparation method of a thermochromic phase-change film with a repairable function comprises the following steps: using a one-step method based on physical casting, with the mass ratio of raw materials polyvinyl alcohol (PVA), boric acid (BA), thermochromic ink (TC) and PEG-8000 being 30:2:1:27, that is, the addition amount of PEG-8000 is 45wt.%, firstly, under the conditions of a stirring temperature of 75°C and a stirring time of 2h, PVA is placed in deionized water for magnetic stirring to obtain a PVA solution, and then 0.2g BA, 0.1g TC and 2.7g PEG-8000 are added to the PVA solution, and magnetic stirring is continued at a stirring temperature of 75°C and a stirring time of 1h to obtain a PBTP mixed solution. Finally, the PBTP solution is placed in a mold for film laying, and then dried at a drying temperature of 60°C and a drying time of 2h, i.e., physical casting, to obtain a thermochromic phase change film PBTP-M with a repairable function, referred to as PBTP-M. The material obtained in specific embodiment 1 is referred to as PBTP-M-45.
[0047] In order to prove the composition of PBTP-M-45, XRD test and FTIR test were carried out. At the same time, PEG-8000 was subjected to FTIR test and XRD test for comparison with PBTP-M-45. The FTIR test results and XRD test results are shown in Figure 2. Figure 1 and Figure 2 As shown, the test results of PBTP-M-45 are the same as those of PEG-8000. The test results show that there is no chemical reaction between PVA and PEG-8000, that is, PVA has no effect on the crystallization behavior of PEG-8000, which can ensure that the composite phase change material has good heat storage capacity; at the same time, the above test proves that PBTP-M-45 was successfully prepared.
[0048] In order to prove the basic morphology of PBTP-M-45, macroscopic tests were performed. The test results are shown in Figure 3 As shown, no obvious white crystals are precipitated on the surface of PBTP-M-45, and each component is evenly dispersed.
[0049] Further SEM test, the test results are as follows Figure 4 As shown in the figure, PEG-8000 is evenly distributed in the film and forms continuous wrinkles.
[0050] In order to prove the shape variability of PBTP-M-45, deformation-recovery test was carried out. The test results are shown in Figure 5 As shown in the figure, PBTP-M-45 can be deformed arbitrarily, and after recovering the deformation, there is no damage or breakage. The test results show that PBTP-M-45 has good shape variability.
[0051] In order to prove the packaging performance of PBTP-M-45, a leak test was conducted, and for comparison, a leak test was conducted on PEG-8000. The specific test method is to heat the sample under the conditions of a heating temperature of 80°C and a heating time of 60 minutes, and observe the material state.
[0052] The test results of PEG-8000 are as follows Figure 6 As shown, PEG-8000 completely melts and flows around;
[0053] The test results of PBTP-M-45 are as follows: Figure 6 As shown, PBTP-45 had no significant changes.
[0054] The test results show that PBTP-M-45 can effectively prevent the leakage of PEG-8000. The reason is that both PVA and PEG-8000 have a large number of hydroxyl groups, which can form hydrogen bonds and chemical bonds between PVA and PEG-8000 at the same time, thereby obtaining anti-leakage performance. Combined with the deformation-recovery test, it can be seen that this type of anti-leakage method based on hydrogen bonds and chemical bonds can maintain the packaging performance after deformation-recovery, which is substantially different from the principle of vacuum impregnation packaging of phase change materials.
[0055] In order to prove that PBTP-M-45 has thermochromic properties, a temperature change test was conducted. The test results are as follows Figure 7 As shown in the figure, at room temperature, PBTP-M-45 is opaque black; at 50°C, PBTP-M-45 changes from opaque black to transparent colorless; when it returns to room temperature, PBTP-45 returns to opaque black. The test results show that PBTP-M-45 has reversible thermochromic properties.
[0056] In order to prove that PBTP-M-45 has the repairable property, a simulated fracture-self-repair test was carried out. The test results are as follows Figure 8 As shown in the figure, after PBTP-M-45 was sheared, the two damaged films were overlapped, water was dripped at the fracture, and then placed in a 60℃ oven for 15 minutes to dry the water. The dried film was taken out and observed, and it was found that the overlapped part had been reconnected without obvious separation; when it was bent, there was no obvious separation at the fracture. The above test results show that PBTP-M-45 has the property of repairability.
[0057] In order to prove the phase change performance of PBTP-M-45, DSC test was carried out. Meanwhile, for comparison, DSC test was carried out on PEG-8000.
[0058] PEG-8000 test results are as follows Fig. 9As shown in Table 1, within the test temperature range of 20 to 100 °C, the melting process of PEG-8000 has an endothermic peak at 60.08 °C with an enthalpy of 160.93 J / g, and the crystallization process has an exothermic peak at 35.29 °C with an enthalpy of 159.13 J / g;
[0059] PBTP-M-45 test results are as follows Fig. 9 As shown in Table 1, within the test temperature range of 20-100°C, the melting process of PBTP-45 has an endothermic peak at 51.97°C with an enthalpy of 74.892 J / g, and the crystallization process has an exothermic peak at 24.38°C with an enthalpy of 72.310 J / g;
[0060] Since the addition amount of PEG-8000 in PBTP-M-45 is 45%, it can be seen from the comparison with the theoretical enthalpy value of PEG-8000 of 45% that the enthalpy value of PBTP-M-45 is slightly greater than the theoretical enthalpy value of PEG-8000. The test results show that the enthalpy of PEG-8000 in the film is fully stored and released.
[0061] Table 1 Phase change enthalpy and temperature of composite phase change materials with different PEG-8000 addition amounts
[0062]
[0063] In order to prove the cycle stability of PBTP-M-45, a cycle test was carried out. The test results are shown in Fig.10 As shown in the figure, the thermal cycling curve of PBTP-M-45 has no significant change in 200 cycles. The test results show that the phase change performance of PBTP-M-45 has no significant change before and after the cycle, which proves that PBTP-M-45 has good cycle stability.
[0064] In order to prove the thermal conductivity of PBTP-M-45, a thermal conductivity test was conducted. At the same time, for comparison, a thermal conductivity test was conducted on PEG-8000.
[0065] PEG-8000 test results are as follows Fig.11 As shown in Table 2, the thermal conductivity of PEG-8000 is 0.2706 W / (m·K);
[0066] PBTP-45 test results are as follows Fig.11 As shown in Table 2, the thermal conductivity of PBTP-M-45 is 0.7417 W / (m·K);
[0067] The test results show that the thermal conductivity of PBTP-M-45 is 174% higher than that of PEG-8000. The reason is that PVA and BA cross-link to form a stable thermal conductivity path, and PEG-8000 is evenly dispersed in the film, which improves the thermal conductivity.
[0068] Table 2 Thermal conductivity of composite phase change materials with different PEG-8000 addition amounts
[0069] Sample name PEG-8000 Example 1 Example 2 Example 3 Comparative Example 1 Thermal conductivity (W / m·K) 0.2706 0.7417 0.8643 0.8440 0.6827
[0070] In order to demonstrate the effect of the amount of PEG-8000 added on the performance, Example 2, Example 3 and Comparative Example 1 are provided, and the composite materials having the amount of PEG-8000 added being 35 wt.%, 40 wt.% and 50 wt.%, respectively.
[0071] Example 2
[0072] A method for preparing a thermochromic phase change film with PEG-8000 added in an amount of 35 wt.%, wherein the steps not specifically described are the same as those in Example 1, except that the amount of PEG-8000 added is 35 wt.%, and the obtained material is named PBTP-M-35.
[0073] The FTIR test results and XRD test results of PBTP-M-35 are shown as follows: Figure 1 and Figure 2 As shown, the test results of PBTP-M-35 are the same as those of PBTP-M-45, that is, there is no substantial difference.
[0074] In order to prove the basic morphology of PBTP-M-35, macroscopic tests were performed. The test results are shown in Figure 3 As shown, no obvious white crystals are precipitated on the surface of PBTP-M-35, and each component is evenly dispersed.
[0075] Further SEM test, the test results are as follows Figure 4 As shown, PEG-8000 is evenly distributed in the film. The difference from PBTP-M-45 is that there are no wrinkles formed by PEG-8000, which indicates that the amount of PEG-8000 added is too small.
[0076] The leak test results of PBTP-M-35 are as follows: Figure 5 As shown, PBTP-M-35 has no obvious change. The test results show that PBTP-M-35 has encapsulation performance and can effectively prevent the leakage of PEG-8000.
[0077] The DSC test results of PBTP-M-35 are as follows: Figure 8 As shown in Table 1, within the test temperature range of 20-100°C, the melting process of PBTP-M-35 has an endothermic peak at 52.31°C with an enthalpy of 56.547 J / g, and the crystallization process has an exothermic peak at 22.67°C with an enthalpy of 55.583 J / g.
[0078] The thermal conductivity test results of PBTP-M-35 are as follows: Fig.10 As shown in Table 2, the thermal conductivity of PBTP-M-35 is 0.8643 W / (m·K).
[0079] Example 3
[0080] A method for preparing a thermochromic phase change film with PEG-8000 added in an amount of 40 wt.%, wherein the steps not specifically described are the same as those in Example 1, except that the amount of PEG-8000 added is 40 wt.%, and the obtained material is named PBTP-M-40.
[0081] The FTIR test results and XRD test results of PBTP-M-40 are as follows: Figure 1 and Figure 2 As shown, the test results of PBTP-M-40 are the same as those of PBTP-M-45, that is, there is no substantial difference.
[0082] In order to prove the basic morphology of PBTP-M-40, macroscopic tests were performed. The test results are shown in Figure 3 As shown, PBTP-M-40 is the same as PBTP-M-35, no obvious white crystals are precipitated on the surface, and the components are evenly dispersed.
[0083] Further SEM test, the test results are as follows Figure 4 As shown in the figure, PEG-8000 is evenly distributed in the film, and wrinkles formed by PEG-8000 begin to appear, but do not cover the entire film. This phenomenon shows that the amount of PEG-8000 added in PBTP-M-40 is increased compared with PBTP-M-35, but still has not reached saturation.
[0084] The leakage test results of PBTP-M-40 are as follows: Figure 5 As shown, PBTP-M-40 has no obvious change. The test results show that PBTP-M-40 has encapsulation performance and can effectively prevent the leakage of PEG-8000.
[0085] The DSC test results of PBTP-M-40 are as follows: Figure 8 As shown in Table 1, within the test temperature range of 20-100°C, the melting process of PBTP-M-40 has an endothermic peak at 53.47°C with an enthalpy of 64.856 J / g, and the crystallization process has an exothermic peak at 23.41°C with an enthalpy of 61.887 J / g.
[0086] The thermal conductivity test results of PBTP-M-40 are as follows: Fig.10 As shown in Table 2, the thermal conductivity of PBTP-M-40 is 0.8440 W / (m·K).
[0087] Comparative Example 1
[0088] A method for preparing a thermochromic phase change film with a PEG-8000 addition amount of 50 wt.%, wherein the steps not specifically described are the same as those in Example 1, except that: the addition amount of PEG-8000 is 50 wt.%, indicating that a white colloidal precipitate appears in the PBTP mixed solution, which indicates that the addition amount of PEG-8000 reaches supersaturation. However, for ease of understanding, the material obtained in Comparative Example 1 is still named PBTP-M-50.
[0089] The FTIR test results and XRD test results of PBTP-M-50 are as follows: Figure 1 and Figure 2 As shown, the test results of PBTP-M-50 are the same as those of PBTP-M-45, that is, there is no substantial difference.
[0090] In order to prove the basic morphology of PBTP-M-50, macroscopic tests were performed. The test results are shown in Figure 3 As shown, the components of PBTP-M-50 are evenly dispersed, but white crystals can be clearly observed on the surface of the film.
[0091] Further SEM test, the test results are as follows Figure 4 As shown in the figure, PEG-8000 is evenly distributed in the film, the wrinkles formed by PEG-8000 are all over the film, and white crystals are precipitated on the surface of the film. This phenomenon shows that the amount of PEG-8000 added to PBTP-M-50 has reached a supersaturated state.
[0092] The leakage test results of PBTP-M-50 are as follows: Figure 5 As shown in the figure, PBTP-M-50 is leaking and liquid is flowing on the surface of PBTP-M-50.
[0093] Combining the results of macroscopic test, SEM test and anti-leakage test, it can be seen that the PEG-8000 loading of PBTP-M-50 is in an oversaturated state.
[0094] The DSC test results of PBTP-M-50 are as follows: Figure 8 As shown in Table 1, within the test temperature range of 20-100°C, the melting process of PBTP-M-50 has an endothermic peak at 53.76°C with an enthalpy of 78.679 J / g, and the crystallization process has an exothermic peak at 24.53°C with an enthalpy of 77.419 J / g.
[0095] The thermal conductivity test results of PBTP-M-50 are as follows: Fig.10 As shown in Table 2, the thermal conductivity of PBTP-M-50 is 0.6827 W / (m·K).
[0096] Through Example 1, Example 2, Example 3 and Comparative Example 1, the following conclusions can be obtained:
[0097] 1. When the addition amount of PEG-8000 is less than 50wt.%, with the increase of the addition amount of PEG-8000, the enthalpy value of PBTP-M increases and the thermal conductivity decreases, but it can still meet the daily enthalpy application requirements. Therefore, the addition amount of PEG-8000 should be as much as possible;
[0098] 2. When the addition amount of PEG-8000 reaches 50wt.%, PBTP-M reaches an oversaturated state, white crystals precipitate and leak, which does not meet the application requirements.
Claims
1. A thermochromic phase change film with repairable function, characterized in that: Using polyvinyl alcohol (PVA) and boric acid (BA) as raw materials for cross-linking, thermochromic ink as the color-changing material, and polyethylene glycol (PEG-8000) as the phase change material, a thermochromic film PBTP-M with repairable function was prepared through a one-step method based on physical casting.
2. The thermochromic phase change film with repairable function according to claim 1, characterized in that: It also has repairable, thermochromic and phase change properties.
3. The thermochromic phase change film with repairable function according to claim 2, characterized in that: The repairable property means that when used as a repairable material, when it is broken or damaged, it can be quickly restored to its original state by adding water and drying.
4. The thermochromic phase change film with repairable function according to claim 3, characterized in that: The repairing operation of the repairable performance is, first, overlapping the damaged film, then dripping water on the overlapping part, and finally drying at a drying temperature of 60° C. for a drying time of 15 minutes, so that the damaged film can be reconnected, that is, repaired.
5. The thermochromic phase change film with repairable function according to claim 2, characterized in that: The thermochromic property, that is, when used as a thermochromic material, under normal temperature conditions, the thermochromic phase change film is in a black and opaque state; When the temperature is higher than 50°C, the thermochromic phase change film is in a colorless and transparent state, that is, when heated above 50°C, the thermochromic phase change film changes from a black opaque state to a colorless and transparent state.
6. The thermochromic phase change film with repairable function according to claim 3, characterized in that: The thermochromic property, i.e., when used as a thermochromic material, is reversible, i.e., after the thermochromic phase change film is changed from a black opaque state to a colorless transparent state by heating, when the temperature is lowered to room temperature, the thermochromic phase change film is restored from the colorless transparent state to the black opaque state.
7. The thermochromic phase change film with repairable function according to claim 2, characterized in that: The phase change performance, that is, when used as a phase change material, the phase change temperature is 22.67-53.76°C, the phase change enthalpy is 55.583-78.679 J / g, and the thermal conductivity is 0.6827-0.8643 W / (m·K).
8. A method for preparing a thermochromic phase change film with a repairable function, characterized in that The following steps are involved: A one-step method based on physical casting is adopted, with raw materials polyvinyl alcohol (PVA), boric acid (BA), thermochromic ink (TC) and PEG-8000 satisfying a certain mass ratio. First, under certain conditions, PVA is placed in deionized water and magnetically stirred to obtain a PVA solution. Then, BA, TC and PEG-8000 are added to the PVA solution, and magnetic stirring is continued under certain conditions to obtain a PBTP mixed solution. Finally, the PBTP solution is placed in a mold for film laying, and then dried under certain conditions, i.e., physical casting, to obtain a thermochromic phase change film PBTP-M with a repairable function, referred to as PBTP-M.
9. The preparation method according to claim 8, characterized in that: In the preparation method, the mass ratio of polyvinyl alcohol PVA, boric acid BA, thermochromic ink TC and PEG-8000 is 30:2:1:27, that is, the addition amount of PEG-8000 is 45wt.%.
10. The preparation method according to claim 8, characterized in that: In the preparation method, the stirring conditions for preparing the PVA solution are: the stirring temperature is 75-80° C., and the stirring time is 1.5-2 h; The conditions for continuing stirring the PBTP mixed solution are as follows: the stirring temperature is 75-80°C and the stirring time is 1-1.5h; In the preparation method, the drying conditions are as follows: the drying temperature is 60° C. and the drying time is 2-2.5 h.
Citation Information
Cited By
Reversible thermochromic composite material based on cellulose nanocrystals and preparation method thereof
CN120758235A